Carbon-based materials as supercapacitor electrodes - Zhang, Li Li; Zhao, X. S. (Chemical Society reviews, 2009)
This tutorial review provides a brief summary of recent research progress on carbon-based electrode materials for supercapacitors, as well as the importance of electrolytes in the development of supercapacitor technology. The basic principles of supercapacitors, the characteristics and performances of various nanostructured carbon-based electrode materials are discussed. Aqueous and non-aqueous electrolyte solutions used in supercapacitors are compared. The trend on future development of high-power and high-energy supercapacitors is analyzed.